Anatomical CT study of lumbar artery perforator flap in women - Olesya Startseva; Igor Reshetov; Jaume Masia; Alexandra Frolova; Elena Mershina; Evgeniya Zhigailova; Mark Gabriyanchik (Chinese Journal of Plastic and Reconstructive Surgery, 2025)
Background: The lumbar artery perforator (LAP) flap is an important autologous option in breast reconstruction. As the lumbar perforator flap is relatively new in this field, several questions remain regarding preoperative preparation, especially concerning computed tomography (CT) and magnetic resonance imaging of the donor site. The objective of this study was to aid the surgical approach to the LAP flap in female patients by precisely determining the characteristics of the lumbar perforators. Methods: We retrospectively reviewed the computed tomographic angiography images of 20 patients who underwent evaluation of the perforator positions from the four lumbar arteries. Four characteristics were studied: length, diameter, path of the lumbar pedicle, and thickness of the tissues available for transfer. Results: We analyzed 20 CT images, identifying 149 perforating vessels of the lumbar artery. The most suitable perforator for flap harvesting was the L4 perforator, which exhibited a larger diameter, a greater number of perforasomes, and a higher percentage of the cutaneous-septal tract. Conclusion: The LAP flap is a viable option for breast reconstruction and as a free flap in women. The L4 perforator artery is the most suitable for harvesting, owing to its superior perfusion capacity, diameter, and course; however, an interposition graft may be required to lengthen the vascular pedicle.